Improving Student Learning Achievement Through Peer Group Teaching Learning Method: Classroom Action Research at State Elementary School 102048 Tanjung Beringin - Iswani, Khairul; Dahliana; Umairhah, Nabila (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning achievement in Islamic religious education learning using the Peer Group Teaching Learning Method. This study uses a type of classroom action research. The design of this study uses the Kemmis & Mctaggart design with four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data were obtained using test and observation techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the Peer Group Teaching Learning Method can improve student learning achievement in Islamic religious education learning with the application of problem-based learning models. This can be seen in cycle I with an average percentage of 50% and in cycle II of 86%. So it can be stated that student activity developed in cycle II. Improving student learning outcomes through the application of the Peer Group Teaching Learning Method on Islamic religious education material was carried out for two cycles. Learning outcomes in cycle I were 66.67% and in cycle II were 76.67%. So it can be stated that student learning outcomes improved better in cycle II. Based on this, the Peer Group Teaching Learning Method can be used as one of the media that can be considered by teachers to overcome the problem of low learning achievement, especially in Islamic religious education learning.